The THE IMPACT OF SENSORY MARKETING ON CONSUMER BEHAVIOR AT STARBUCKS MANADO - Estefan Dusauw; Maryam Mangantar; Merinda H.C. Pandowo (Universitas Sam Ratulangi, 2023)
This study aims to analyze the impact of sensory marketing towards consumer behavior at Starbucks Manado. This research applies qualitative method. Population were 20 retained customers of Starbucks Manado that went to Starbucks at least three times a month. For sampling technique, applies purposive sampling. The findings of the research using the interview approach yielded four indicators of sensory marketing that influence the behavior of Starbucks Manado’s consumer. Sight, sound, taste, and smell all have an impact on consumers’ psychology, personal, and social that affects their behavior. These studies might be excellent references for those interested in learning the use of sensory marketing, as well as a body of knowledge and practical implications. Keywords: sensory marketing, consumer behavior, sight, sound, taste, smell, psychology, personal, social